2010
DOI: 10.1098/rsta.2010.0224
|View full text |Cite
|
Sign up to set email alerts
|

Electron–electron and electron–hole pairing in graphene structures

Abstract: The superconducting pairing of electrons in doped graphene owing to in-plane and outof-plane phonons is considered. It is shown that the structure of the order parameter in the valley space substantially affects conditions of the pairing. Electron-hole pairing in a graphene bilayer in the strong coupling regime is also considered. Taking into account retardation of the screened Coulomb pairing potential shows a significant competition between the electron-hole direct attraction and their repulsion owing to vir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…There are nevertheless important differences, one of the most prominent ones being the lack of an intermediate energy scale between the gap and the Fermi energy which in conventional superconductivity is provided by the Debye frequency. In the present case the screened interaction crosses over as a function of frequency from the statically screened values at zero frequency to the unscreened Coulomb potential at frequencies on the order of the momentum-transfer dependent plasmon energies 11 , which vanish at large wavelengths in two-dimensional electron systems. Since the momentum transfer for scattering at the Fermi surface can take values q ∈ [0, 2k F ], the small momentum transfer region is particularly poorly described by a statically screened interaction.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are nevertheless important differences, one of the most prominent ones being the lack of an intermediate energy scale between the gap and the Fermi energy which in conventional superconductivity is provided by the Debye frequency. In the present case the screened interaction crosses over as a function of frequency from the statically screened values at zero frequency to the unscreened Coulomb potential at frequencies on the order of the momentum-transfer dependent plasmon energies 11 , which vanish at large wavelengths in two-dimensional electron systems. Since the momentum transfer for scattering at the Fermi surface can take values q ∈ [0, 2k F ], the small momentum transfer region is particularly poorly described by a statically screened interaction.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This problem has been studied previously using a variety of approaches and approximations [7][8][9][10][11] . To our knowledge only one study has accounted for the dynamic nature of screening 11 , and none have accounted simultaneously for the reduction of screening 12 that accompanies the appearance of an interlayer coherence gap.…”
Section: Introductionmentioning
confidence: 99%
“…24-33. It was shown that both weak and strong coupling regimes of the pairing are achievable experimentally. 24 Estimates of the critical temperature T c at strong coupling [25][26][27][28][29][30] are very dependent on the model and approximations used, ranging from room temperature, with the unscreened Coulomb attraction taken as a pairing potential, 25,26 to unobservably small values given by Bardeen-Cooper-Shrieffer (BCS) theory with screened interaction. 27 The pairing in a graphene bilayer at strong coupling was argued 28,29,33 to involve both conduction and valence bands of electrons and holes, i.e., it is multiband.…”
Section: Introductionmentioning
confidence: 99%
“…27 A study of the problem, taking into account the effects of the frequency dependence of the gap and the pairing potential, was presented in Ref. 30.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in the electronic bilayer systems, those mentioned phase transitions are indistinguishable as it was shown in references [12,21]. On the other hand, the inclusion of the dynamic screening and the full band structure favors the pairing and condensation [25][26][27].…”
Section: Introductionmentioning
confidence: 76%